THE INFLUENCE OF ENVIRONMENTAL, SOCIAL, GOVERNANCE & INSTITUTIONAL OWNERSHIP ON FIRMVALUE WITH FIRM SIZE AS A MODERATION VARIABLE - Aisyah Ayu Sigit Wijaya; Herry Subagyo; Nila Tristiarini; Amron Amron; Piji Pakarti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Firm value reflects the firm's capacity to improve efficiency and strategy in resource utilization; various aspects are capable of encouraging an increase in firm value, including environmental, social, governance, and institutional ownership. Recent PricewaterhouseCoopers (PwC) Indonesia data illustrates this transformation in corporate reporting practices. As of December 30, 2022, 653 listed companies submitted their 2021 Sustainability Reports, representing 79% of all listed companies. This marked a dramatic 324% increase compared to the 154 companies that produced such reports in 2021 (www.pwc.com). This substantial growth demonstrates the rapidly evolving corporate landscape where sustainability reporting has transitioned from an optional practice to an essential business component. Methods: The research applies a quantitative approach, utilizes saturated sampling, and analyzes the data using panel data regression. Results: The finding that environmental, social, and governance affect the value of the firm's ESG Leader Index. Firm size moderates the effect of environmental, social, and governance factors on firm value, and firm size is unable to moderate the influence of institutional ownership on firm value. Keywords: Environmental Social Governance, Institutional Ownership, Firm Value, Firm Size, ESG Leader Index